Estimates of heritability and phenotypic correlations of several characters, in four natural mutants in soybeans - Gilioli, João Luiz; Sediyama, Tuneo; Silva, José Carlos; Thiébaut, José Tarcisio Lima; Reis, Múcio Silva (Pesquisa Agropecuaria Brasileira, 2014)
Heritability and phenotypic correlations were estimated for several characters in four F2 populations of soybeans. These F2 populations were derived from the crosses among the varieties 'Paraná', 'São Luiz', 'Viçoja' and 'Hardee' with their respective natural mutants of later flowering and maturation date, Paranagoiana, PR77-1000l, UFV-1, and IAC74-2736-10. The estimates of heritability for plant height at flowering in the four crosses were greater than the estimates at maturation showing that for the same character there exist phases in the development of soybeans where the application of selection may be more effective. For the cross Paraná x Paranagoiana, a positive correlation was obtained between the characters height of insertion of the first leaf and height of first pod, showing a relationship between leaf x pod for these genotypes.